Risk of Toxicity After Initiating Immune Checkpoint Inhibitor Treatment in Patients With Rheumatoid Arthritis. Issue 7 (October 2021) - Efuni, Elizaveta; Cytryn, Samuel; Boland, Patrick; Niewold, Timothy B.; Pavlick, Anna; Weber, Jeffrey; Sandigursky, Sabina
Abstract : Introduction: Immune checkpoint inhibitors (ICIs) are increasingly used to treat advanced cancer. Rheumatoid arthritis (RA) is associated with an increased risk of malignancies; however, patients with RA have been excluded from ICI trials. In this study, we evaluated risk of toxicity after initiation of ICI treatment in RA patients. Methods: We conducted a single-institution, medical records review analysis to assess the incidence of immune-related adverse events (irAEs) and autoimmune disease (AID) flares among patients with AIDs treated with ICIs from 2011 to 2018. A subgroup analysis for RA patients was performed with frequencies of irAEs and AID flares reported. Results: Twenty-two patients with RA who were treated with ICI for malignancy were identified. At the time of ICI initiation, 86% had inactive RA disease activity. Immune-related adverse events occurred in 7 (32%) of patients, with 2 (9%) developing grade 3 (i.e., severe) irAEs. Immune checkpoint inhibitors were temporarily discontinued because of irAEs in 5 patients (23%), and permanently in 1 patient. Rheumatoid arthritis flares occurred in 12 patients (55%). Of those, 10 (83%) received oral corticosteroids with an adequate treatment response. Conclusions: Our analysis suggests that irAEs following ICI treatment are not increased among RA patients compared with other cancer patients. Heightened RA disease activity during ICI treatment is common, but most adverse events are manageable with oral corticosteroids, and few require permanent ICI discontinuation. A close collaboration between the oncologist and rheumatologist is advisable when considering ICIs in patients with RA.